Task force report: Scales for screening and evaluating tremor: Critique and recommendations. Issue 13 (3rd September 2013) - Elble, Rodger; Bain, Peter; João Forjaz, Maria; Haubenberger, Dietrich; Testa, Claudia; Goetz, Christopher G.; Leentjens, Albert F. G.; Martinez‐Martin, Pablo; Pavy‐Le Traon, Anne; Post, Bart; Sampaio, Cristina; Stebbins, Glenn T.; et al.
ABSTRACT: The Movement Disorder Society established a task force to review rating scales for the assessment of tremor. Screening instruments used in identifying patients with tremor were also reviewed. Seven tremor severity scales, six activities of daily living (ADL)/disability scales, four quality‐of‐life scales, and five screening instruments were identified by searching PubMed.gov. The availability, use, acceptability, reliability, validity, and sensitivity to change were reviewed for each scale; and each scale was classified as recommended, suggested or listed based on whether 3, 2, or 1 of the following criteria were met: (1) used in the assessment of tremor (yes/no), (2) used in published studies by people other than the developers (yes/no), and (3) successful clinimetric testing (yes/no). Five tremor severity scales (the Fahn‐Tolosa‐Marin Tremor Rating Scale, the Bain and Findley Clinical Tremor Rating Scale, the Bain and Findley Spirography Scale, the Washington Heights‐Inwood Genetic Study of Essential Tremor Rating Scale, and the Tremor Research Group Essential Tremor Rating Assessment Scale), one ADL/disability scale (the Bain and Findley Tremor ADL Scale), one quality‐of‐life scale (the Quality of Life in Essential Tremor Questionnaire), and one screening instrument (the Washington Heights‐Inwood Genetic Study of Essential Tremor Rating Scale, version 1) are recommended using these criteria. However, all scales need a more comprehensive analysis of sensitivity to change in order to judge their utility in clinical trials and individual patient assessments. The task force recommends that further work with existing recommended scales be performed as opposed to the development of new tremor scales. © 2013 International Parkinson and Movement Disorder Society